Six Sigma (DMAIC) Practices In School Discipline Management System - Ahmad Tajudin, Mohd Khairil Amri (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
There are a few of weaknesses in the school discipline management system especially in terms of allocation of time, allocation of money, human resources and policy making because of the inefficiency in quality management procedures. The use of six sigma approach as a tool for process improvement can assist to overcome all these weaknesses through a process of reducing the error in the process. However, the use of six sigma is still not widely applied in the organizations especially in the educational service sector. In DMAIC approach are consists of define, measure, analyze, improve, and control is a systematic approach to improve the process by focusing on reducing the change process and also can deduct any error in the school discipline management process and increase customer satisfaction. The purpose of this research is to identify the implementation of DMAIC approach in the school discipline management system and also assist the researcher to identify the potential of consistent process improvement.